Penerapan Teknologi Mesin Pencacah Sampah Organik Sebagai Upaya Peningkatan Kualitas Pupuk Kompos Pada KSM Srimenanti Jaya Sungailiat - Ristika Oktavia Asriza; Nurhadini Nurhadini; Verry Andre Fabiani; Fahmi Rizal (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
Currently, special efforts are needed to create proper and efficient waste management. The formation of a waste bank or through self-help groups is an effort to improve the community’s economy by taking advantage of the waste problems that are around. The Srimenanti Jaya Non-Governmental Organization (KSM) is a group that cares about environmental conditions and waste problems. KSM Srimenanti Jaya has helped the community and government in efforts to handle household waste into compost. Through this community service activity, counseling and simple technology are provided in the form of a garbage chopping machine to facilitate the process of processing waste into compost. To speed up the composting process, it is necessary to enumerate the waste into smalller sizes with a garbage chopper machine. The manufacture of this garbage chopping machine is designed with a shredder mechanism where the inserted waste will be attacted, cut, and chopped so that it becomes small pieces. Through the knowledge and technology generated from this activity, it is hoped that KSM Srimenanti Jaya can produce compost that has a selling value and is compotitive in the market